Implementation of HLMS to Support the Development of Digital Education Services - Rofiuddin Rofiuddin; Busro Akramul Umam; Fitri Aulia; Nabil Qistubillah (Universitas Nurul Jadid, 2026)
The rapid growth of digital education services requires organizations to adopt integrated and adaptive learning systems. However, PT Unggul Mediatama Indonesia, as a digital-based startup, did not yet have an internal learning platform, and learning activities were conducted using fragmented tools such as separate communication platforms and non-centralized content distribution. This condition caused difficulties in managing learning materials, monitoring participant progress, and ensuring consistent service delivery, highlighting the urgency of implementing a centralized system. This community service activity aims to implement a Hybrid Learning Management System (HLMS) to support digital education services and improve the partner’s digital readiness. The activity applied a technology-based participatory approach combined with an Agile-oriented development process, including needs analysis through observations and interviews, system design, frontend development using React JS, backend integration using Laravel via API, testing, and validation. The results show that the HLMS was successfully developed as a web-based platform integrating structured and self-directed learning. Evaluation using a Likert-scale questionnaire involving five respondents (one company leader and four IT team members) resulted in an average score of 4.30, categorized as “very appropriate”. The implementation improved learning management, enhanced digital readiness, and transformed learning practices into an integrated system, demonstrating the effectiveness of HLMS in supporting digital education services.